STEPS TO USE SOCIAL ASSISTANCE IMPACT WITH COVID-19 AHEAD OF ELECTIONS AS A MEANS OF SOCIALIZATION AND EARLY 2021 CAMPAIGN IN MAINTAINING THE POSITION AS REGIONAL HEAD IN INDONESIA - Yusuf, Anas; Junaedi, Junaedi; Hardi, Rudi; Gustaf Said, Try (IJBLE Scientific Publications Community Inc., 2023)
Until now, Indonesia has not implemented a lockdown policy to break the chain of the virus. This phenomenon is giving a big blow, especially from a social point of view, nowadays with the implementation of everything done at home (stay at home and work from home). The packaging is beautiful and attractive for the social assistance mafia related to Covid-19 which is packed with PSBB or other activities carried out by the Governor/Regent/Mayor/Village Head (kuwu/lurah) and ASN, which are inconsistent with the use of Integrated Social Welfare Data (DTKS) and non-DTKS data in providing Social Assistance (Bansos) to the community to overcome the impact of the coronavirus pandemic (Covid-19) may be subject to Law no. 20 of 1999 as amended by Law no. 20 of 2001 concerning Eradication of Corruption Article 2 paragraph (2) and Article 3 Subsidiary Article 372 of the Criminal Code with a penalty of 4 (four) years in prison. Participation and actions that must be carried out by Bawaslu and law enforcers (KPK and other agencies) who are competent in enforcing the law for unscrupulous regional heads, both incumbents, PLTs with their positions, their authority to store Covid-19 aid packaged with social assistance via PSBB can be convicted